2022
DOI: 10.1038/s41398-022-02206-3
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional analysis of behavior predicts genotype with high accuracy in a mouse model of Angelman syndrome

Abstract: Angelman syndrome (AS) is a neurodevelopmental disorder caused by loss of expression of the maternal copy of the UBE3A gene. Individuals with AS have a multifaceted behavioral phenotype consisting of deficits in motor function, epilepsy, cognitive impairment, sleep abnormalities, as well as other comorbidities. Effectively modeling this behavioral profile and measuring behavioral improvement will be crucial for the success of ongoing and future clinical trials. Foundational studies have defined an array of beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…Prior work has demonstrated that integrating performance across various behavioral assays can lead to more sensitive and reliable measures of the overall socalled "emotionality" of preclinical rodent models. 9,13,38,90 Whether this same approach would apply for injury-induced negative affect is unclear. To determine whether a normalized "emotionality" behavioral z-score could reflect chronic neuropathic injury, we next tested this concept by normalizing each individual output from a single behavioral assay (eg, % time in center and distance travelled in the open field; Table 1) into a single assay score.…”
Section: Integrated Behavioral Scores Provide Emergent Painrelated Ou...mentioning
confidence: 99%
“…Prior work has demonstrated that integrating performance across various behavioral assays can lead to more sensitive and reliable measures of the overall socalled "emotionality" of preclinical rodent models. 9,13,38,90 Whether this same approach would apply for injury-induced negative affect is unclear. To determine whether a normalized "emotionality" behavioral z-score could reflect chronic neuropathic injury, we next tested this concept by normalizing each individual output from a single behavioral assay (eg, % time in center and distance travelled in the open field; Table 1) into a single assay score.…”
Section: Integrated Behavioral Scores Provide Emergent Painrelated Ou...mentioning
confidence: 99%
“…For multidimensional analysis of behavior profiles, we performed data selection, standardization, principal component analysis (PCA), k-means clustering, and validation (Fig. 2b) (Popovitz et al, 2021;Tanas et al, 2022). We utilized PUMBAA (phenotyping using a multidimensional behavioral analysis algorithm, https://github.com/sidorovlab/PUMBA A) for all multidimensional analysis (Tanas et al, 2022).…”
Section: Multidimensional Analysis Of Trajectoriesmentioning
confidence: 99%
“…2b) (Popovitz et al, 2021;Tanas et al, 2022). We utilized PUMBAA (phenotyping using a multidimensional behavioral analysis algorithm, https://github.com/sidorovlab/PUMBA A) for all multidimensional analysis (Tanas et al, 2022).…”
Section: Multidimensional Analysis Of Trajectoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…The exception to that was in the more challenging operant tasks (i.e., FR3 and PR; Figures 6-9). Prior work has demonstrated that integrating performance across various behavioral assays can lead to more sensitive and reliable measures of the overall so-called 'emotionality' of preclinical rodent models [9,12,35,78]. Whether this same approach would apply for injury-induced negative affect is unclear.…”
Section: Integrated Behavioral Scores Provide Emergent Pain-related O...mentioning
confidence: 99%